Simulation and prediction of uptake, distribution, and exhalation of organic solvents. Issue 1 (January 1974) - Fiserova-Bergerova, Vera; Vlach, Jiri; Singhal, Kishore
Abstract : Fiserova-Bergerova, Vera, Vlach, J., and Singhal, K. (1974). British Journal of Industrial Medicine, 31, 45-52. Simulation and prediction of uptake, distribution, and exhalation of organic solvents. Presented here is a theory and mathematical solution of the uptake, distribution, and excretion of inhaled lipid soluble noxious gases, which embraces the effects of metabolism. An electrical analogue was employed to explain the theory, since the analogue is described by the same set of differential equations, and much knowledge is available for the mathematical treatment of electrical networks. The model is used to calculate the uptake and exhalation curves of vapours, to explain what happens to the inhaled vapours in the body, and to predict their cumulation in the body in periodic situations such as occur in industrial exposure.